Role of dorsal root ganglion K(2P)1.1 in peripheral nerve injury-induced neuropathic pain - Mao, Qingxiang (Mol Pain, 2017)
Peripheral nerve injury-caused hyperexcitability and abnormal ectopic discharges in the primary sensory neurons of dorsal root ganglion (DRG) play a key role in neuropathic pain development and maintenance. The two-pore domain background potassium (K(2P)) channels have been identified as key determinants of the resting membrane potential and neuronal excitability. However, whether K(2P) channels contribute to neuropathic pain is still elusive. We reported here that K(2P)1.1, the first identified mammalian K(2P) channel, was highly expressed in mouse DRG and distributed in small-, medium-, and large-sized DRG neurons. Unilateral lumbar (L) 4 spinal nerve ligation led to a significant and time-dependent reduction of K(2P)1.1 mRNA and protein in the ipsilateral L4 DRG, but not in the contralateral L4 or ipsilateral L3 DRG. Rescuing this reduction through microinjection of adeno-associated virus-DJ expressing full-length K(2P)1.1 mRNA into the ipsilateral L4 DRG blocked spinal nerve ligation-induced mechanical, thermal, and cold pain hypersensitivities during the development and maintenance periods. This DRG viral microinjection did not affect acute pain and locomotor function. Our findings suggest that K(2P)1.1 participates in neuropathic pain development and maintenance and may be a potential target in the management of this disorder.